2021
DOI: 10.3389/fmicb.2021.769884
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Nutrition and Psychoneuroendocrineimmune Modulation: Relevance for COVID-19 in BRICS Nations

Abstract: The consequences of COVID-19 are not limited to physical health deterioration; the impact on neuropsychological well-being is also substantially reported. The inter-regulation of physical health and psychological well-being through the psychoneuroendocrineimmune (PNEI) axis has enduring consequences in susceptibility, treatment outcome as well as recuperation. The pandemic effects are upsetting the lifestyle, social interaction, and financial security; and also pose a threat through perceived fear. These conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 156 publications
(393 reference statements)
0
3
0
Order By: Relevance
“…Similarly, high mortality rates after SARS-CoV-2 infection have been observed in patients with schizophrenia (Nemani et al, 2021). Interactions between the brain and immune system, already known from psycho-neuro-immunological research, have been observed in the COVID-19 pandemic (Mehta et al, 2021).…”
Section: Introductionmentioning
confidence: 88%
“…Similarly, high mortality rates after SARS-CoV-2 infection have been observed in patients with schizophrenia (Nemani et al, 2021). Interactions between the brain and immune system, already known from psycho-neuro-immunological research, have been observed in the COVID-19 pandemic (Mehta et al, 2021).…”
Section: Introductionmentioning
confidence: 88%
“…Uptake of lipid moieties from exterior their exterior is shown to affect the cancer cell physiology and assist in upholding stemness in a variety of malignancies. Moreover, the import of FA into cytosol has a critical impact on the malignant transformation of cells ( 87 , 111 ). Research investigations have shown that lipid uptake is upregulated in lymphoma cells ( 96 ).…”
Section: Lipid Sequestration In T-cell Malignanciesmentioning
confidence: 99%
“…Studies have shown that the ecological footprint of BRICS countries is decreasing, which means that green health may become a new priority [ 57 ]. There is also growing concern about mental health in BRICS countries, which has been exacerbated by the COVID-19 pandemic [ 58 ]. Furthermore, with more people moving into the cities, the health challenges brought by urbanization should also be noticed.…”
Section: Possible Pathways For Brics Future Health Cooperationmentioning
confidence: 99%